ANALYSIS OF DOCUDRAMA HISTORY AND REFERENTIAL RECONSTRUCTION OF SANG KIAI MOVIES: ADAPTATION OF BIOGRAPHICAL HISTORIOGRAPHIC TEXTS TO BIOPIC FILM - Kartika, Bambang Aris; Prihatini, Nanik S.; Hastanto, Sri; Dharsono, D., (Seni Media Rekam ISI Surakarta, 2019)
This article discusses about the conception of adaptation of biographical historiographic texts into the medium text in the Sang Kiai film which is a type of historical docudrama film. Adaptation conception shows a transposition pattern of content from historical biographical narrative texts constructed into the text medium of Sang Kiai film. By conducting a study on the Sang Kiai film through approaches of adaptation and heuristic, hermeneutic, and internal criticism methodology has produced a pattern of referential reconstruction in the production of historical genre film texts, especially in the types of biopic films. The Sang Kiai film is a moving picture biography of the K.H. Hasyim Asy'ari figure who narrated historical facts about the nationalism of the founder of the Nahdlatul Ulama (NU) against the colonialist hegemony of Japanese and Allied fascist armies. Thus, the docudrama film which is positioned as a document of visualization of the historical facts about the past that is presented today through the reproduction of historical texts in the biopic film medium. The pattern of referential reconstruction shows that the biopic film of the Sang Kiai is a representation of the truth of the biographical facts of the K.H. Hasyim Asy'ari figure, although it was produced and presented through historical fiction film text